NrCAM regulating neural systems and addiction related behaviors - Ishiguro, Hiroki (2012)
We have previously shown that a haplotype associated with decreased NrCAM expression in brain is protective against addiction vulnerability for polysubstance abuse in humans and that Nrcam knockout mice do not develop conditioned place preferences for morphine, cocaine, or amphetamine. In order to gain insight into NrCAM involvement in addiction vulnerability, which may involve specific neural circuits underlying behavioral characteristics relevant to addiction, we evaluated several behavioral phenotypes in Nrcam knockout mice. Consistent with a potential general reduction in motivational function, Nrcam knockout mice demonstrated less curiosity for novel objects and for an unfamiliar conspecific, showed also less anxiety in the zero maze. Nrcam heterozygote knockout mice reduced alcohol preference and buried fewer marbles in home cage. These observations provide further support for a role of NrCAM in substance abuse including alcoholism vulnerability, possibly through its effects on behavioral traits that may affect addiction vulnerability, including novelty seeking, obsessive compulsion and responses to aversive or anxiety-provoking stimuli. Additionally, in order to prove glutamate homeostasis hypothesis of addiction, we analyzed glutamatergic molecules regulated by NRCAM. Glutaminase appears to be involved in NrCAM-related molecular pathway in two different tissues from human and mouse. An inhibitor of the enzyme, PLG, treatment produced, at least, some of the phenotypes of mice shown in alcohol preference and in anxiety-like behavior. Thus, NrCAM could affect addiction-related behaviors via at least partial modulation of some glutamatargic pathways and neural function in brain.